Sign Language Interpreter - Dogra, Astha; Malik, Ketan; Chowdary, Vinay (International Journal of Engineering and Technology, 2018)
The world’s population now stands at 7.6 billion. Out of these, millions of people are not blessed with the ability to hear or/and speak. Although speech becomes a barrier between these people and other abled persons but, there are three types of sign languages which help to decrease this gap. There are about 250 types of sign language interpreters which translate their language for other people. This paper describes a similar type of device aimed to facilitate a bridge between the two groups of population. It develops a wearable device having motion detecting sensors to sense the orientation and direction of fingers in order to recognize the gesture made by the user. Also, it transmits the gesture to a wireless display unit through a Bluetooth module which displays the corresponding word to the gesture made on an LCD. Thus, in this way, sign-to-text conversion is carried out. The heart of the device is Atmega328 with flash memory of 32k bytes enabling us to store a wide range of words. The designed system was capable to recognize the pre-stored gestures according to ASL (American Sign Language). Prototype was designed for one hand and it was tested on a few gestures.